Mistresses MacIver and Dabdoub Nasser Shake Hands - Richardson, Steven D P (Petits Propos Culinaires, 2012)
The author describes experimenting with a kitchen pepper recipe found in Cookery and Pastry, As Taught and Practised by Mrs MacIver: teacher of those arts in Edinburgh. A New Edition (1789) which he uses in a crossover dish in the recipe for meat and pea stew, Yakhnet bazela, found in Christiane Dabdoub Nasser’s Classic Palestinian Cookery and in other recipes.